Identification of a secreted casein kinase 1 in Leishmania donovani: effect of protein over expression on parasite growth and virulence. - Mary Dan-Goor (Public Library of Science (PLoS), 2013)
Casein kinase 1 (CK1) plays an important role in eukaryotic signaling pathways, and their substrates include key regulatory proteins involved in cell differentiation, proliferation and chromosome segregation. The Leishmania genome encodes six potential CK1 isoforms, of which five have orthologs in other trypanosomatidae. Leishmania donovani CK1 isoform 4 (Ldck1.4, orthologous to LmjF27.1780) is unique to Leishmania and contains a putative secretion signal peptide. The full-length gene and three shorter constructs were cloned and expressed in E. coli as His-tag proteins. Only the full-length 62.3 kDa protein showed protein kinase activity indicating that the N-terminal and C-terminal domains are essential for protein activity. LdCK1.4-FLAG was stably over expressed in L. donovani, and shown by immunofluorescence to be localized primarily in the cytosol. Western blotting using anti-FLAG and anti-CK1.4 antibodies showed that this CK1 isoform is expressed and secreted by promastigotes. Over expression of LdCK1.4 had a significant effect on promastigote growth in culture with these parasites growing to higher cell densities than the control parasites (wild-type or Ld:luciferase, P<0.001). Analysis by flow cytometry showed a higher percentage, ∼4-5-fold, of virulent metacyclic promastigotes on day 3 among the LdCK1.4 parasites. Finally, parasites over expressing LdCK1.4 gave significantly higher infections of mouse peritoneal macrophages compared to wild-type parasites, 28.6% versus 6.3%, respectively (p = 0.0005). These results suggest that LdCK1.4 plays an important role in parasite survival and virulence. Further studies are needed to validate CK1.4 as a therapeutic target in Leishmania.